THE MAIN FACTORS OF BUILDING A MODERN FAMILY - Mominova , Dilnoza Solekhovna (Educational Research in Universal Sciences, 2023)
The article presents the issues of preparing young people for independent family life in a modern family, increasing the level of literacy of parents in the field of family education. The necessary recommendations regarding modern family factors are given.